Practical experiences with modelling and forecasting time series - Jenkins, Gwilym M. (St. Helier : Gwilym Jenkins and Partners (Overseas) Ltd., 1979)
This volume is based on lectures given by the author during the Institute of Statisticians Conference on Forecasting at the Kings College Cambridge in July, 1976.
Bibliography: p. 124-125.
lje 24/01/2019
Loans
Keywords: Time-series analysis; Business forecasting--Mathematical models; Economic forecasting--Mathematical models